Pendidikan Islam di Era Disrupsi Abad ke-21 - Fitri Ekawati Mamonto; M. Nurul Humaidi (Global Education Journal, 2026)
The acceleration of technology in the 21st-century era of disruption and the transition toward the BANI (Brittle, Anxious, Non-Linear, Incomprehensible) framework confront Islamic Education with complex existential challenges, impacting both student morality and institutional readiness. This study aims to map the primary challenges of Islamic Education, identify emerging trends in curriculum innovation and learning methodologies, and formulate contemporary educator competency standards relevant to modern demands. Employing a systematic literature review approach, this study analyzed 20 empirical journal articles on Islamic Education published between 2019 and 2026. The findings reveal that the core challenges center on digital moral disorientation among students and limited technological infrastructure. In response, a strategic shift has emerged toward reconstructing holistic-integralistic curricula that merge science and religion, optimizing instructional digital ecosystems such as AI and online platforms, and establishing tripartite collaborations with families. Furthermore, a new consensus demands that Islamic Education teachers transform into agents of religious moderation by mastering techno-pedagogical skills and employing an interdisciplinary approach that integrates Sufism values with digital literacy. Ultimately, this study concludes that navigating the era of disruption requires a dynamic harmonization between cyber-technological acceleration and moral-spiritual resilience to foster a globally competitive generation of insan kāmil (the perfect human)